An e-health intervention to support the transition of young people with long-term illnesses to adult healthcare services: Design and early use. Issue 9 (September 2016) - Coyne, I.; Prizeman, G.; Sheehan, A.; Malone, H.; While, A.E.
Highlights: Successful transition to adult healthcare requires information and preparation. Adolescents receive limited information about transition. Digital technologies may help engage adolescents in their healthcare. Innovative online resource developed through a participatory iterative process. www.SteppingUP.ie provides information and guidance for transition. Abstract: Objective: Co-design information and website to support adolescents and young adults with long-term illnesses in their transition to adult healthcare. Methods: A participatory iterative process involving a survey (n = 207), twenty-one interviews, six participatory workshops, six video recordings, two advisory groups, and a co-design group to identify needs and preferences for e-health and information provision, was used to develop an appropriate intervention. Results: Adolescents and young people expressed preferences for information that was trustworthy, empowering, colorful, easily downloaded online and written using non-patronizing language. They desired video testimonials of experiences from young adults who had transitioned to adult healthcare and wanted advice about becoming more independent, managing their condition, preparing for the transition, and information about medications and the differences between child and adult healthcare. They also wanted information about the location and configuration of adult healthcare, key hospital personnel, and frequently asked questions. Conclusion: The participatory iterative process led to the development of an online resource specifically tailored to the adolescents and young people's transition needs and information preferences. Preliminary feedback indicates that it is a valued resource. Practice implications: Thewww.SteppingUP.ie website has the potential to help prepare its target population group for the transition to adult healthcare.